The Kecerdasan Emosional sebagai Strategi Koping Stress pada Siswa yang sedang Menjalani Pembelajaran Daring - Slamet Hamid; Wahyu Utama (Neolectura, 2022)
This study aims to determine the relationship between emotional intelligence and coping stress strategies in online learning. This research used quantitative research with correlational methods. The sample was 50 students. The results showed that a significant positive relationship between emotional intelligence and coping strategies, this was shown by a product moment correlation value of 0.816 with a significance level of 0.00. The results showed that the relationship between emotional intelligence and coping stress strategies was in the moderate category.